HEALTH IMPACT CAUSED BY POOR WATER AND SANITATION IN DISTRICT ABBOTTABAD - Jabeen, Sadia; Mahmood, Qaisar; Tariq, Sumbal; Nawab, Bahadar; Elahi, Noor (Journal of Ayub Medical College Abbottabad, 2011)
Background: Large proportions of people still do not have excess to safe drinking water and proper sanitation. Methods: Qualitative and quantitative approaches were used to assess the health impacts. Random households were selected. Information was collected from questionnaire through interview schedule method, group discussion and observation checklist. Results: People rated water and sanitation condition in urban as: 10% very good, 27% good, 20% bad, 43% very bad, and none of them said we don’t know. While in rural areas they rated 10% very good, 36% good, 44% bad, 6% very bad, and 4% of them said we don’t know. Water sources in selected urban and rural areas were different, 37% in urban and 68% in rural area depended on bore wells as water source, 22% depended on hand pumps. In urban areas, the disease ratio was typhoid 20%, hepatitis 13%, diarrhoea 27%, skin infection 23%, stomach problems 53% and allergies 33%. In rural areas, after stomach problems, diarrhoea, hepatitis and typhoid ratio was very high as compared to urban area. In rural community, 70% were unaware of poor water and sanitation consequences on health. Conclusion: The water and sanitation condition in urban as well as in rural community is poor but in rural community it is even worse. The drinking water was contaminated with E. coli, Enterobacter, Salmonella and Clostridium. This observation was correlated with prevalence of many water born diseases especially in rural communities of Abbottabad. Keywords: Safe drinking water, health impacts, environmental awareness, water borne diseases, water and sanitation.